A portrait of the visual arts : meeting the challenges of a new era - McCarthy, Kevin F., 1945- (RAND Corp., 2005)
Providing information about developments in the visual arts world, this book promotes analysis of the sector, describing the characteristics of visual arts consumers (collectors and appreciators), artists, finances, and organizations. It also tells a story of rapid, even seismic change, systemic imbalances, and dislocation.